1995
DOI: 10.4319/lo.1995.40.3.0556
|View full text |Cite
|
Sign up to set email alerts
|

Concentration of mercury species in relationship to other site‐specific factors in the surface waters of northern Wisconsin lakes

Abstract: To investigate relationshi.Qs between mercury speciation and site-specific factors in temperate freshwaters, we measured the concentration of seven Hg species along with 18 environmental variables in the surface waters of 23 northern Wisconsin lakes during spring and fall. The lakes spanned relatively wide gradients in Hg (0.15-4.8 ng liter ') and methylmercury (MeHg: 0.04-2.2 ng liter-I). Over the range ofmeasured variables, Hg and MeHg were most strongly correlated with each other (r2 = 0.83-0.88) and with d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
114
0

Year Published

1997
1997
2016
2016

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 208 publications
(127 citation statements)
references
References 29 publications
(30 reference statements)
13
114
0
Order By: Relevance
“…This finding is in agreement with previous data based on culture and the most probable number which identified SRB and FeRB in the Babeni Reservoir (Bravo et al 2014) as well as with another study showing SRB and FeRB coexistence in sediments (Yu et al 2012). The greatest methylation activity is often found just below the oxic/anoxic transition zone in sediments underlying oxygenated water (Watras et al 1995;Ullrich et al 2001;Bravo et al 2014). where both sulfate and iron reduction rates can be high.…”
Section: Discussion Dispersion and Fate Of Hg In Downstream Reservoirsmentioning
confidence: 99%
“…This finding is in agreement with previous data based on culture and the most probable number which identified SRB and FeRB in the Babeni Reservoir (Bravo et al 2014) as well as with another study showing SRB and FeRB coexistence in sediments (Yu et al 2012). The greatest methylation activity is often found just below the oxic/anoxic transition zone in sediments underlying oxygenated water (Watras et al 1995;Ullrich et al 2001;Bravo et al 2014). where both sulfate and iron reduction rates can be high.…”
Section: Discussion Dispersion and Fate Of Hg In Downstream Reservoirsmentioning
confidence: 99%
“…Natural accumulation of heavy metals in a lake environment (e.g. Watras et al 1995(from Bodaly et al 1993), Harris and Bodaly 1998); 2. High methylation rates within the bottom anoxic water layer of the lake caused by sulfur-reducing bacteria activity (Boudou et al 2006); 3.…”
Section: Fishmentioning
confidence: 99%
“…Watras et al (1995b) found that on average, 80% of THg passed 0.45-mm filters in epilimnetic water from 23 lakes in Wisconsin. As already noted, organic matter decomposition would result in higher [THg] SE , provided that Hg is more conservative than the organic matter during sediment diagenesis.…”
Section: Thg In the Surface Sediment And The Settling Mattermentioning
confidence: 99%